(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Coccinella septempunctata L. was found as a major preadator of mustard aphid (Lipaphiserysimi Kalt.). The maximum activity of Coccinella septempunctata recorded in the last week of Februaryand started declining towards the first week of March due to high temperature and maturity of the cropduring the study period.